Phytoplankton adapt to changing ocean environments - Irwin, A.J., Finkel, Z.V., Müller-Karger, F.E. and Troccoli-Ghinaglia, L. (My University, 2015)
Model projections indicate that climate change may dramatically restructure phytoplankton communities, with cascading consequences for marine food webs. It is currently not known whether evolutionary change is likely to be able to keep pace with the rate of climate change. For simplicity, and in the absence of evidence to the contrary, most model projections assume species have fixed environmental preferences and will not adapt to changing environmental conditions on the century scale. Using 15 y of observations from Station CARIACO (Carbon Retention in a Colored Ocean), we show that most of the dominant species from a marine phytoplankton community were able to adapt their realized niches to track average increases in water temperature and irradiance, but the majority of species exhibited a fixed niche for nitrate. We do not know the extent of this adaptive capacity, so we cannot conclude that phytoplankton will be able to adapt to the changes anticipated over the next century, but community ecosystem models can no longer assume that phytoplankton cannot adapt.
Keywords: climate change, evolution, phytoplankton, realized niches